1989
DOI: 10.1037/1040-3590.1.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Assessing cognitive coping strategies for acute postsurgical pain.

Abstract: The Cognitive Coping Strategy Inventory (CCSI), developed from a theoretical taxonomy of coping strategies, allows for the assessment of coping strategies in acute pain settings. The initial instrument was administered to 83 postsurgical patients, and acceptable internal consistency was obtained for the subscales. After minor revisions it was administered to 100 postsurgical patients, a concurrent validity study was conducted, and its factor structure was investigated. The final version of the inventory was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1
3

Year Published

1992
1992
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 21 publications
3
29
1
3
Order By: Relevance
“…These results confirm and extend previous research in which catastrophizing was found to be associated with more intense pain following a variety of elective surgery procedures (Butler et al, 1989). In order to assess the generalizability of these results, future research should consider the impact that catastrophizing may have on other forms of acute clinical pain (e.g., pain during childbirth).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These results confirm and extend previous research in which catastrophizing was found to be associated with more intense pain following a variety of elective surgery procedures (Butler et al, 1989). In order to assess the generalizability of these results, future research should consider the impact that catastrophizing may have on other forms of acute clinical pain (e.g., pain during childbirth).…”
Section: Discussionsupporting
confidence: 89%
“…Cognitive coping and catastrophizing were assessed using the Cognitive Coping Strategies Inventory (CCSI; Butler et al, 1989). Following the standard instructions, patients rated how often they used each of 70 identified strategies for dealing with pain (e.g., "I take myself very far away from the pain by using my imagination.").…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Catastrophizing-The Catastrophizing scale of the Cognitive Coping Strategies Inventory (Butler, Damarin, Beaulieu, Schwebel, & Thorn, 1989) was designed to measure catastrophizing in response to pain. The Fatigue Catastrophizing Scale was developed by substituting the word fatigue for pain in the instructions and item content .…”
Section: Methodsmentioning
confidence: 99%
“…This average fatigue score showed high internal consistency across the four measurement points (α = .91-.93). Previous research has demonstrated the reliability and validity of the Fatigue Symptom Inventory in women diagnosed with breast cancer (Broeckel et al, 1998;Hann et al, 1998 Catastrophizing-The Catastrophizing scale of the Cognitive Coping Strategies Inventory (Butler, Damarin, Beaulieu, Schwebel, & Thorn, 1989) was designed to measure catastrophizing in response to pain. The Fatigue Catastrophizing Scale was developed by substituting the word fatigue for pain in the instructions and item content .…”
mentioning
confidence: 99%